Association of Physical Fitness and Diet with Body Weight in Austrian Adolescents - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objectives: Physical fitness and diet along with body weight are key determinants of health. Excess body weight, poor dietary choices, and low physical fitness, however, are becoming increasingly prevalent in adolescents. In order to develop adequate intervention strategies, additional research on potential interaction effects of these entities is needed. Therefore, this study examined the combined association of physical fitness and diet with body weight in Austrian adolescents. Methods: A total of 164 (56% male) adolescents between 11 and 14 years of age completed the German Motor Test, which consists of eight items that assess cardiorespiratory endurance, muscular endurance and power, speed and agility, flexibility, and balance, along with body weight and height measurements. Additionally, participants completed a standardized food frequency questionnaire. Results: Spearman correlation analyses showed an inverse association between physical fitness and processed foods consumption (rho = −0.25, p < 0.01), while sweet consumption was positively associated with physical fitness (rho = 0.17, p = 0.03). No significant interaction effects between diet and physical fitness on body weight were observed. However, both higher physical fitness and greater sweet consumption were associated with lower body weight (p < 0.01). Conclusions: The present study emphasizes the independent and combined interactions of key correlates of health. It also suggests that high fitness may offset detrimental effects of poor dietary choices. In order to address potential health risks early in life and facilitate future health and well-being, it is important to monitor and control physical fitness, diet, and body weight during adolescence. © 2024 by the authors.
Keywords: motor competence; physical activity; eating behavior; dietary pattern; body composition; youth